Forest cover and climate as potential drivers for dengue fever in Sumatra and Kalimantan 2006–2016: a spatiotemporal analysis. Issue 7 (3rd June 2019) - Husnina, Zida; Clements, Archie C. A.; Wangdi, Kinley
Abstract: Objectives: To describe and quantify spatiotemporal trends of dengue fever at district level in Sumatra and Kalimantan, Indonesia in relation to forest cover and climatic factors. Methods: A spatial ecological study design was used to analyse monthly surveillance data of notified dengue fever cases from January 2006 to December 2016 in the 154 districts of Sumatra and 56 districts of Kalimantan. A multivariate, zero‐inflated Poisson regression model was developed with a conditional autoregressive prior structure with posterior parameters estimated using Bayesian Markov chain Monte Carlo simulation with Gibbs sampling. Results: There were 230 745 cases in Sumatra and 132 186 cases in Kalimantan during the study period. In Sumatra, the risk of dengue fever decreased by 9% (95% credible interval [CrI] 8.5–9.5%) for a 1% increase in forest cover and by 12.2% (95% CrI 11.9–12.6%) for a 1% increase in relative humidity. In Kalimantan, dengue fever risk fell by 17.6% (95% CrI 17.1–18.1%) for a 1% increase in relative humidity and rose by 7.6% (95% CrI 6.9–8.4%) for a 1 °C increase in minimum temperature. There was no significant residual spatial clustering in Sumatra after accounting for climate and demographic variables. In Kalimantan, high residual risk areas were primarily centred in North and East of the island. Conclusions: Dengue fever in Sumatra and Kalimantan was highly seasonal and associated with climate factors and deforestation. Incorporation of climate indicators into risk‐based surveillance might be warranted for dengue fever in Indonesia. Abstract : Objectifs: Décrire et quantifier les tendances spatiotemporelles de la fièvre dengue au niveau du district à Sumatra et à Kalimantan, en Indonésie, en relation avec la couverture forestière et les facteurs climatiques. Méthodes: Un schéma d'étude écologique spatiale a été utilisé pour analyser les données de surveillance mensuelles des cas notifiés de fièvre dengue de janvier 2006 à décembre 2016 dans les 154 districts de Sumatra et 56 districts de Kalimantan. Un modèle de régression de Poisson multivarié à inflation de zéro a été développé avec une structure antérieure autorégressive conditionnelle avec des paramètres postérieurs estimés à l'aide de la simulation bayésienne de Monte Carlo à chaîne de Markov avec échantillonnage de Gibbs. Résultats: Il y avait 230.745 cas à Sumatra et 132.186 cas à Kalimantan au cours de la période de l'étude. A Sumatra, le risque de fièvre dengue a diminué de 9% (intervalle de confiance à 95% [IC] de 8, 5 à 9, 5%) pour une augmentation de 1% de la couverture forestière et de 12, 2% (IC95%: 11, 9‐12, 6%) pour une augmentation de 1% de l'humidité relative. A Kalimantan, le risque de fièvre dengue a diminué de 17, 6% (IC95%: 17, 1‐18, 1%) pour une augmentation de 1% de l'humidité relative et a augmenté de 7, 6% (IC95%: 6, 9‐8, 4%) pour une augmentation de 1°C de la température minimale. Après la prise en compte des variables climatiques et démographiques, aucun regroupement spatial résiduel n'était significatif à Sumatra. A Kalimantan, les zones à risque résiduel élevé étaient principalement situées dans le nord et dans l'est de l'île. Conclusions: La fièvre dengue à Sumatra et à Kalimantan était très saisonnière et associée aux facteurs climatiques et à la déforestation. L'intégration d'indicateurs climatiques dans la surveillance fondée sur les risques pourrait être justifiée pour la fièvre dengue en Indonésie.